A possible role for HLA-DRB1*04:06 in statin-related myopathy in Japanese patients. Issue 6 (December 2016) - Sai, Kimie; Kajinami, Kouji; Akao, Hironobu; Iwadare, Mizuho; Sato-Ishida, Ryoko; Kawai, Yasuyuki; Takeda, Kenji; Tanimoto, Takashi; Yamano, Takashi; Akasaka, Takashi; Ishida, Tatsuro; Hirata, Ken-ichi; et al.
Abstract: Statin-related myopathy (SRM) is a clinically important adverse reaction. Recent pharmacogenetic research, mainly in non-Asian populations, have indicated clinical relevance of some of genetic biomarkers to SRM, but predictive markers for SRM in Asian populations including Japanese has not yet been established. This study was aimed to identify clinically important genetic markers associated with SRM in Japanese patients. Allele frequencies of the three reported candidate markers — SLCO1B1 rs4149056, RYR2 rs2819742, and GATM rs9806699 — and carrier frequencies of HLA types were compared between patients with SRM patients (n = 52) and healthy Japanese subjects (n = 2878 or 86 (for rs9806699) as controls). No significant association of RYR2, SLCO1B1, and GATM variants with SRM were observed in our Japanese patients, but a significant association was detected for HLA-DRB1*04:06 with SRM (odds ratio: 3.19; 95% confidence interval: 1.53–6.66). This study suggested that HLA-DRB1*04:06 might be associated with SRM onset in a Japanese population. Further studies are required to validate these results.